Single cell multi-omic analysis identifies key genes differentially expressed in innate lymphoid cells from COVID-19 patients - Kaushik, Abhinav; Chang, Iris; Han, Xiaorui; He, Ziyuan; Komlosi, Zsolt I.; Ji, Xuhuai; Cao, Shu; Akdis, Cezmi A.; Boyd, Scott; Pulendran, Bali; Maecker, Holden T.; Davis, Mark M.; et al. (Frontiers in Immunology, 2024)
Introduction Innate lymphoid cells (ILCs) are enriched at mucosal surfaces where they respond rapidly to environmental stimuli and contribute to both tissue inflammation and healing. Methods To gain insight into the role of ILCs in the pathology and recovery from COVID-19 infection, we employed a multi-omics approach consisting of Abseq and targeted mRNA sequencing to respectively probe the surface marker expression, transcriptional profile and heterogeneity of ILCs in peripheral blood of patients with COVID-19 compared with healthy controls. Results We found that the frequency of ILC1 and ILC2 cells was significantly increased in COVID-19 patients. Moreover, all ILC subsets displayed a significantly higher frequency of CD69-expressing cells, indicating a heightened state of activation. ILC2s from COVID-19 patients had the highest number of significantly differentially expressed (DE) genes. The most notable genes DE in COVID-19 vs healthy participants included a) genes associated with responses to virus infections and b) genes that support ILC self-proliferation, activation and homeostasis. In addition, differential gene regulatory network analysis revealed ILC-specific regulons and their interactions driving the differential gene expression in each ILC. Discussion Overall, this study provides mechanistic insights into the characteristics of ILC subsets activated during COVID-19 infection.